Seismic analysis of RC building frames with vertical mass and stiffness irregularities using adaptive pushover analysis - Benaied, Brahim; Hemsas, Miloud; Benanane, Abdelkader; Hentri, Mohammed (Revista de la Construcción. Journal of Construction, 2023)
Irregular multistory buildings constitute a large part of modern urban infrastructure due to architectural aesthetics and functional requirements. In contrast, their behavior during recent major earthquakes indicated that severe structural damage was observed due to non-uniform distributions of mass, stiffness and strength either in plan or in elevation. Notably, abrupt changes in these quantities between adjacent stories are always associated with changes in the structural system along the height of the building. The present study investigates the inelastic response of RC buildings with mass and stiffness irregularities subjected to earthquake action. Thus, the displacement-based adaptive pushover method is used. This latter is motivated by the application of a lateral displacement pattern obtained by combining different mode shapes and updated incrementally at each analysis step. For this purpose, a ten-story regular frame structure is chosen and modified by incorporating vertical irregularities in various forms in order to estimate and quantify essential parameters’ responses. The results obtained are discussed under the following headings: base shear forces, roof displacement, inter-story drift and story-shear distribution. With respect to the vertical mass and stiffness irregularities, it was noticed that the seismic response is more significantly influenced by stiffness irregularities compared to mass irregularities, which were found to have a slight impact on the seismic behavior of the building. It is also established that the simple procedure allows the evaluation of design forces and displacements in a more rational manner, in accordance with the current state of knowledge and modern trends in building codes. The results conclude, however, that the irregular structure cannot meet the seismic design requirements and must be constructed to minimize seismic effects.